Choosing the "Best" surgical techniques for mitral valve repair: Lessons from the literature. Issue 8 (18th June 2019) - Chemtob, Raphaelle A.; Wierup, Per; Mick, Stephanie; Gillinov, Marc
Abstract: Mitral valve (MV) repair is the procedure of choice to correct mitral regurgitation caused by degenerative MV disease, due to its well‐documented superiority over MV replacement. Repair of the MV is feasible in more than 95% of such patients and restores valve function and preserve ventricular function. Surgeons choose from a wide variety of mitral repair techniques, with the ultimate procedure based upon the pathology and the particular surgeon's personal preference. As a result, there is considerable controversy concerning choice of repair techniques and prostheses (ie, annuloplasty device). This targeted review of available data concerning repair of the degenerative valve will inform surgeon decision‐making in MV repair.